Failure to listen to the whispering: Proverbs 12:24–28 in times of femicide epidemic - Uroko, Favour C. (Verbum et ecclesia, 2025)
This study aims to examine Proverbs 12:24–28 considering the increasing rates of femicide in Nigeria. Various approaches have been employed to address the issue of femicide in the country. Numerous girls and women have been killed by their intimate partners and spouses, with this alarming trend appearing to escalate between 2024 and 2025. Scholars have examined this issue from sociological, legal and political perspectives; however, the problem continues to worsen. This study approaches femicide from a religious perspective, drawing themes from wisdom literature, particularly from the book of Proverbs. Literary analysis was used to analyse data obtained from the Bible, biblical commentaries, real-time examples from newspapers and gazettes, complemented by relevant academic literature. The aphorisms in Proverbs 12:24–28 address themes of diligence, hard work, anxiety, good companionship and longevity. Three primary themes emerged from the analysis: (1) industriousness; (2) interpersonal approach and managing pressure; and (3) friendship dynamics. The pericope also emphasises the importance for women to exercise caution regarding the types of relationships they enter. Based on these findings, recommendations are presented and discussed.Intradisciplinary and/or interdisciplinary implicationsThe study shows that laziness, anxiety, a lack of contentment, harsh words and bad friends are aphorisms in Proverbs 12:24–28 that are liable for the increasing femicide in Nigeria. The Old Testament and practical theology were implicated in this study.